The influence of social variables and moral disengagement on prosocial and antisocial behaviours in field hockey and netball - Boardley, I. D.; Kavussanu, M. (Journal of Sports Sciences, 2009)
In this study, we examined: (a) the effects of perceived motivational climate and coaching character-building competency on prosocial and antisocial behaviours towards team-mates and opponents in field hockey and netball; (b) whether the effects of perceived character-building competency on sport behaviours are mediated by moral disengagement; and (c) whether these relationships are invariant across sport. Field hockey (n = 200) and netball (n = 179) players completed questionnaires assessing the aforementioned variables. Structural equation modelling indicated that mastery climate had positive effects on prosocial and negative effects on antisocial behaviour towards team-mates, while performance climate had a positive effect on antisocial behaviour towards team-mates. Perceived character-building competency had a positive effect on prosocial behaviour towards opponents and negative effects on the two antisocial behaviours; all of these effects were mediated by moral disengagement. No effect was found for prosocial behaviour towards team-mates. The model was largely invariant across sport. The findings aid our understanding of social influences on prosocial and antisocial behaviours in sport.